Adjunctive simvastatin for treatment-resistant depression: study protocol of a 12-week randomised controlled trial. Issue 1 (January 2019) - Husain, Muhammad I.; Chaudhry, Imran B.; Khoso, Ameer B.; Husain, Mohammad Omair; Rahman, Raza R.; Hamirani, Munir M.; Hodsoll, John; Carvalho, Andre F.; Husain, Nusrat; Young, Allan H.
Abstract : Background: A third of patients diagnosed with major depressive disorder (MDD) experience treatment-resistant depression (TRD). Relatively few pharmacological agents have established efficacy for TRD. Therefore, the evaluation of novel treatments for TRD is a pressing priority. Statins are pleiotropic agents and preclinical studies as well as preliminary clinical trials have suggested that these drugs may have antidepressant properties. Aims: To report on a protocol for a 12-week, randomised, double-blind, placebo-controlled trial of add-on treatment with simvastatin for patients meeting DSM-5 criteria for MDD who have failed to respond to at least two adequate trials with approved antidepressants. The trial has been registered with Clinicaltrials.gov in (ClinicalTrials.gov identifier: NCT03435744). Method: After screening and randomisation to the two parallel arms of the trial, 75 patients will receive simvastatin and 75 patients will receive placebo as adjuncts to treatment as usual. The primary outcome is change in Montgomery–Åsberg Depression Rating Scale scores from baseline to week 12 and secondary outcomes include changes in scores on the 24-item Hamilton Rating Scale for Depression, the Clinical Global Impression scale, the 7-item Generalized Anxiety Disorder scale and change in body mass index from baseline to week 12. Assessments will take place at screening, baseline, and weeks 2, 4, 8 and 12. Checklists for adverse effects will be undertaken at each visit. Simvastatin (20 mg) will be given once daily. Other secondary outcomes include C-reactive protein and plasma lipids measured at baseline and week 12. Results: This trial will assess simvastatin's efficacy and tolerability as an add-on treatment option for patients with TRD and provide insights into its putative mechanisms of action. Conclusions: As the first trial investigating the use of simvastatin as an augmentation strategy in patients with TRD, if the results indicate that adjuvant simvastatin is efficacious in reducing depressive symptoms, it will deliver immediate clinical benefit. Declaration of interest: I.B.C. and N.H. have given lectures and advice to Eli Lilly, Bristol Myers Squibb, Lundbeck, Astra Zeneca and Janssen pharmaceuticals for which they or their employing institution have been reimbursed. R.R. and M.M.H. have received educational grants and support for academic meetings from Pfizer, Roche, Novartis and Nabiqasim. A.H.Y. has been commissioned to provide lectures and advice to all major pharmaceutical companies with drugs used in affective and related disorders. A.H.Y. has undertaken investigator-initiated studies from Astra Zeneca, Eli Lilly, Lundbeck and Wyeth. None of the companies have a financial interest in this research.